Shaft resistance of model pile in dry silt - Shahin, Mohamed M. (2006)
A test apparatus to measure the load transfer along the shaft of a model pile inserted in a specimen of silt is described.This apparatus allows independent control of the boundary stresses of a cylindrical silt specimen in the vertical and horizontal directions.The load transfer along the shafts of smooth and rough surfaces aluminium model piles in dry silt under static load was measured.The pile installation technique used was designed to minimize soil disturbance so that the failure criterion for pile shaft friction could be investigated.The study shows the importance of the boundary conditions of the soil specimen surrounding the model pile.The study also shows the effectiveness of using rough pile in increasing the pile capacity.The magnitude of pile-displacement at failure which necessary to mobilize the ultimate shaft resistance varies significantly with the surface roughness of the pile.The results show that the angle of the pile-silt contact depends on the roughness of the pile surface, initial density, void ratio and horizontal confining pressure